Religion and Counter-Narratives of Hoax about COVID-19: Enhancing the Role of Youth Interfaith in Bukittinggi - Zulfan Taufik (Dialogia, 2022)
This article aimed to analyze the relationship between religion and hoax related to the COVID-19 pandemic, particularly the role of interfaith youth in countering negative narratives developed in Bukittinggi, West Sumatra. In the context of a religious community like Bukittinggi, religion is one of the constructive instruments that must be considered. This research used the action research method. This research began with mapping the condition of hoaxes related to COVID-19 in Bukittingi through three Focus Group Discussions (FGD). Researcher was also involved with partners in intervening through local training activities to strengthen the capacity of interfaith youth to respond to hoaxes. This research showed that apart from religious leaders, interfaith youths play an essential role in breaking the chain of hoaxes related to COVID-19 through counter-narratives. In addition, this research showed a trend of positive change in interfaith youth, from being only passive objects of COVID-19 hoaxes to being active agents who carry out hoax counter-narratives through various media. As the dominant population in Indonesia that is so massive in the use of the internet and social media, young people have great potential to become 'victims' of hoax narratives. However, with the increasing number of digital literacies received by young people, they also have great potential to become agents who can break the chain of hoaxes.